Bibliometric Performance Analysis for Online Assessment in Health Education - Ahmad, Rahwan; Hariawan, Hamdan; Ratna; Prasetyawati (Babali Publisher, 2025)
Background: Online assessment has become a crucial component of health professional education, a trend significantly accelerated by the COVID-19 pandemic. This study presents a comprehensive bibliometric analysis of scientific publications on online assessment in health education indexed in Scopus from 2004 to 2024. Methods: The data were cleaned using OpenRefine and analyzed with Biblioshiny. Results: Findings from 339 selected articles revealed that the United States was the leading country in publication output. Gary M. Velan and Rakesh K. Kumar were identified as the most productive authors, while BMC Medical Education emerged as the top journal. Keyword analysis highlighted the prominence of terms such as “health education,” “online assessment,” and “e-learning,” indicating the evolving research focus in this field. Furthermore, the mapping demonstrated strong international collaboration networks, particularly between the United States and the United Kingdom. Conclusion: This study provides valuable insights into the developmental trajectory and dynamics of research on online assessment in health education and identifies key opportunities for future exploration. It recommends integrating cross-database analyses (e.g., WoS, PubMed) and employing mixed bibliometric approaches to capture a broader research landscape.